A comprehensive high resolution data collection for tropospheric water vapor assessment for the Upper Rhine Graben, Germany - Benjamin Fersch; Bettina Kamm; Endrit Shehaj; Andreas Wagner; Peng Yuan; Gregor Möller; Andreas Schenk; Alain Geiger; Stefan Hinz; Hansjörg Kutterer; Harald Kunstmann (PANGAEA, 2021)
Different observation and modeling techniques were used to derive integrated water vapor (IWV) fields for the Upper Rhine Graben in the border region of Germany, Switzerland, and France. The dataset features 1) point-scale IWV and zenith total delay (ZTD) derived for 66 stations of the global navigation satellite system (GNSS) Upper Rhine Graben network (GURN), 2) area-distributed IWV and differential slant path delays from space-borne Interferometric synthetic aperture radar (InSAR) observations, 3) IWV, ZTD, refractivity (3D), and water vapor density (3D) from tomography, obtained by collocation of GNSS and InSAR products, and 4) IWV, precipitation and water vapor density (3D) simulated with the Weather Research and Forecasting Modeling system (WRF) with free run (open-loop) and three-dimensional variational data-assimilation (3D-VAR) configuration. All data products cover 4 seasonal epochs (11 – 22 Apr 2016, 13 – 24 Jul 2018, 16 – 31 Oct 2018, 06 – 21 Jan 2017). GNSS, InSAR, and tomography data are additionally available for the period Jan 2015 – Jun 2019.